Literasi LITERASI DIGITAL DALAM MENANGKAL INFODEMIK COVID 19 DI MEDIA SOSIAL - Fauzi (QAULAN : Jurnal Komunikasi dan Penyiaran Islam, 2020)
This research aims to describe the infodemic flow of Covid 19 on social media and aspects of digital literacy in accessing information. This research use desciptive qualitative approach. The method used is the literature study method. Based on this method, the authors collected data using the note-taking technique to review documentation in the form of books, research journals, literature and other library materials on digital literacy. The results show that the infodemic flow of Covid 19 on social media is getting stronger and more worrying. The Indonesian National Police (Polri) have handled at least 51 cases of hoax content related to COVID-19. Likewise, data from the Ministry of Communication and Informatics (Kemenkominfo) noted that during the Covid-19 pandemic there were 554 hoaxes spread across 1,209 digital platforms. Because social media has the power to influence public opinion. The infodemic flow of Covid 19 on social media has had an even greater impact than the outbreak itself, namely public panic. Infodemics have become a global problem, including in Indonesia, which must be overcome with digital literacy. Ease of accessing information through digital media must be accompanied by competence in critical thinking. Through digital literacy competences can evaluate reliable sources of information.